Increased Punishment for Repeat Offenders of Motor Vehicle Theft: Case Study at Polsek Medan Timur, Indonesia - Elsa Wendelyna Sinaga; D. Debora (Manunggal Halim Jaya, 2026)
This study examines the effectiveness of a policy that increases the prison term for repeat offenders of motor vehicle theft by one-third, with a research focus at the Medan Timur Police Station. The study employs a normative-empirical legal approach, examining the provisions on aggravated punishment in the Criminal Code and Law Number 1 of 2023 concerning the National Criminal Code, in conjunction with empirical data from interviews and case documents from the 2023–2025 period. The results of the study show that, normatively, the policy of adding one-third to the prison term has a clear legal basis. However, in law enforcement practice, this policy has not been implemented optimally and consistently, especially at the investigation stage. Empirical data indicate that the rate of recidivism for motor vehicle theft at the Medan Timur Police Station remains fluctuating and tends to increase in 2025, despite the implementation of provisions for aggravated punishment. This condition indicates a gap between legal norms and their implementation, so that the policy of increasing penalties is more reactive than preventive. This study confirms that the effectiveness of punishment for repeat offenders is not only determined by the severity of criminal sanctions, but also requires integration with non-penal strategies, including systematic data collection on repeat offenders, consistency in law enforcement, and strengthening of rehabilitation and social reintegration programs.